Some New Remarks about the Dynamics of an Automobile with Two Trailers - Camelia Petrişor (Journal of Applied Mathematics)
The goal of our paper is to complete some results presented by Craioveanu et al. (1998) concerning the nonlinear stability of the equilibrium states of the car with two trailers’ dynamics. In addition, the Lax formulation, numerical integration via Lie-Trotter, and Kahan’s integrator for these dynamics are presented.